Maternal embryonic leucine zipper kinase (MELK) optimally regulates the HIV-1 uncoating process - Nishiyama, Takara; Takada, Toru; Takeuchi, Hiroaki; Iwami, Shingo (Journal of theoretical biology, 2022)
•Modeling the process of core structure uncoating by MELK.•Quantifying the uncoating process in HIV-1 cDNA synthesis and nuclear trafficking.•In silico simulation results show that MELK optimally regulates the HIV-1 uncoating process. Human immunodeficiency virus type-1 (HIV-1) attaches to target cells and releases the capsid, an essential component of the viral core that contains viral RNA, into the cytoplasm. After invading target cells, the core structure gradually collapses. The timing of the disassembly of the HIV-1 capsid is essential for efficient viral cDNA synthesis and transport into the nucleus. HIV-1 uncoating is controlled by the host factor maternal embryonic leucine zipper kinase (MELK); however, the quantitative and dynamic relationship between the HIV-1 uncoating process and HIV-1 infection remains unresolved. In this study, we quantified the uncoating process on HIV-1 cDNA synthesis and transport into the nucleus by combining a mathematical model with in vitro data. In addition, detailed in silico simulations demonstrated host factors, including MELK, optimize transport efficiency. Our experimental-mathematical approach revealed quantitative dynamics of the HIV-1 uncoating process, indicating that increasing the speed of uncoating always reduces the amount of HIV-1 cDNA in the nucleus.